A framework for N-of-1 trials of individualized gene-targeted therapies for genetic diseases - Kim-McManus, Olivia; Gleeson, Joseph G.; Mignon, Laurence; Smith Fine, Amena; Yan, Winston; Nolen, Nicole; Demarest, Scott; Berry-Kravis, Elizabeth; Finkel, Richard; Leonard, Stefanie; Finlayson, Samuel; Augustine, Erika; et al. (Nature Communications, 2024)
Individualized genetic therapies - medicines that precisely target a genetic variant that may only be found in a small number of individuals, as few as only one - offer promise for addressing unmet needs in genetic disease, but present unique challenges for trial design. By nature these new individualized medicines require testing in individualized N-of-1 trials. Here, we provide a framework for maintaining scientific rigor in N-of-1 trials. Building upon best practices from traditional clinical trial design, recent guidance from the United States Food and Drug Administration, and our own clinical research experience, we suggest key considerations including comprehensive baseline natural history, selection of appropriate clinical outcome assessments (COAs) individualized to the patient genotype-phenotype for safety and efficacy assessment over time, and specific statistical considerations. Standardization of N-of-1 trial designs in this fashion will maximize efficient learning from this next generation of targeted individualized therapeutics.